Perceived Impact of Oral Health Conditions - Hillary L. Broder, PhD, MEd; Gary Slade, BDSc, DDPH, PhD; Rufus Caine, DMD, MPH; Susan Reisine, PhD (Blackwell Synergy, 2000)
This study assessed the perceived impact of oral health conditions, and the relationship of two measures of self-reported outcome, the RAND SF-36 and the Oral Health Impact Profile (OHIP), to clinical indicators of oral health among inner-city adolescents.